2019
DOI: 10.1016/j.supflu.2019.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Amidophosphonate ligands as cerium extractants in supercritical CO2

Abstract: Industrial-scale rare earth extraction is typically performed by liquid-liquid extraction with large amounts of solvents, acids and organophosphorus ligands. An alternative is to use these extractants in supercritical CO 2 (SC-CO 2), where the crucial operating parameter is their solubility. Different molecules with amidophosphonate backbones have been synthesized and investigated in view of improving their solubility in SC-CO 2 and thereby their cerium extraction capacity. The CO 2-philicity of these extracta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Although TFPC6 possesses a fluorinated chain longer than that of TFPC4, it exhibits marginally diminished solubility at 4.62 mmol/mol COd 2 . According to Bouali et al, 34 the solubility values indicate the decreasing trend in solubility with increasing molar mass in the amidophosphonate extracts (Figure 3). Specifically, 2-ethylhexylamine has the highest molecular mass and lowest solubility among the listed extractants.…”
Section: Synthesis Of Extractant: Tris(perfluoroalkyl)phosphate (Tfp)mentioning
confidence: 82%
See 2 more Smart Citations
“…Although TFPC6 possesses a fluorinated chain longer than that of TFPC4, it exhibits marginally diminished solubility at 4.62 mmol/mol COd 2 . According to Bouali et al, 34 the solubility values indicate the decreasing trend in solubility with increasing molar mass in the amidophosphonate extracts (Figure 3). Specifically, 2-ethylhexylamine has the highest molecular mass and lowest solubility among the listed extractants.…”
Section: Synthesis Of Extractant: Tris(perfluoroalkyl)phosphate (Tfp)mentioning
confidence: 82%
“…In this study, we have chosen the solid scCO 2 process to compare the extraction capacity of TFPs with modified extractants with an amidophosphonate backbone, which have been well studied in the solid scCO 2 process. 34 The protocol for the preparation of the solid matrix {cotton/La(NO 3 ) 3 } has been previously detailed in refs 34 and 35. Typically, lanthanum(III) nitrate hexahydrate was dissolved in ultrapure water to give an aqueous solution with a lanthanum concentration of 0.1 mol/L.…”
Section: Synthesis Of Tfpmentioning
confidence: 99%
See 1 more Smart Citation
“…If, however, more purification or elemental separation must be performed, additional process steps are required such as: (i) chlorination using safer agents such as NH 4 Cl [220,221]; (ii) advanced leaching [222][223][224][225][226][227][228][229][230][231][232][233][234][235][236]; (iii) or even bioleaching using bacteria which avoids the use of strong acids [237]; (iv) hydrometallurgy (solid-liquid or liquid-liquid extraction) [15,210,[238][239][240][241][242][243][244]; as well as (v) electrodeposition at the reduction step, including in ionic liquids [245][246][247][248][249][250][251][252][253] and molten salts [254][255][256][257][258][259], with their wide electrochemical stability [260].…”
Section: Rare-earth Elementsmentioning
confidence: 99%
“…Development of radionuclide-containing materials is an emerging area of research, as recently indicated by alarming public and scientific reports focusing on challenges in nuclear waste reprocessing and management that must be addressed in the upcoming years. One of the cornerstones for handling these challenges properly and in a timely manner is a fundamental understanding of corresponding radionuclide-related chemical processes and actinide-containing material design strategies. Metal–organic frameworks (MOFs) as tunable, versatile, modular, and well-defined platforms provide unique capabilities, many of which are inaccessible in other porous supports. For instance, in addition to large surface areas and internal void spaces, MOFs provide the opportunity to integrate actinides inside the structure through metal node extension, cation exchange in the secondary building units (SBUs), or coordination to the capping linkers (i.e., chelation to organic linkers installed after framework formation). All of these pathways for actinide integration can be realized, even within one strategically engineered framework. , Moreover, the use of these concepts for the development of MOF-based “single-use” actinide sensors to detect volatile radioactive species, multifaceted materials for selective radionuclide sequestration, or actinide-containing catalysts for waste reprocessing are attractive directions in the technological sector that could address urgent demands for more efficient nuclear waste management . Furthermore, MOFs are crystalline materials with tailorable capabilities, which allow for a structure–property correlation to be constructed through framework design, and, more importantly, connect material properties and performance with structural changes on the atomic level.…”
Section: Introductionmentioning
confidence: 99%